E-Government Implementation in the Village General Administrative Electronic System (SEDULUR) Program - Hery Nariyah; Nursahidin Nursahidin; Darwanto Darwanto; Agus Purwanto; Ade Setiadi; Moh Sutarjo (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: E-government is one of the government's efforts to develop the implementation of electronic-based government activities in order to improve the quality of service to various parties effectively and efficiently. In the context of implementing e-government in Cirebon City, Cirebon City is carrying out a smart city or smart city movement with its vision of realizing Cirebon as a creative, innovative, synergistic and competitive smart city in 2028. Lots of programs have been implemented as supporters of the realization of the smart city movement in the city of Cirebon. Research with the title "Implementation of E-government in the Village Public Administration Electronic System Program (SEDULUR) in Kalijaga Village, Harjamukti District, Cirebon City", has a formulation of the problem of how to implement the sedulur program in Kalijaga Village, Harjamukti District, Cirebon City. Design/methodology/approach: This research uses a case study method with a qualitative approach that is descriptive. Determination of informants using purposive sampling. The theoretical foundation used is the Balanced E-government Scorecard theory with five dimensions in it, the five dimensions are: benefits, efficiency, participation, transparency, and change management. Findings: Based on the research that has been done, it is concluded that the implementation of e-government in Kalijaga Village, Harjamukti District, Cirebon City with case studies of the sedulur program has not been optimal in its implementation, this is because the sedulur program still wants to be developed so that later all people can access it without having to contact the head of the RW First of all, it's just that the budget was diverted during the Covid-19 pandemic which hampered the development of the Sedulur program. Practical implications: The efforts that have been made are with Harjamukti District supporting government programs related to people who are aware and obedient of paying taxes so that revenue-sharing funds (DBH) from these taxes can be allocated for the development of the sedulur program. Paper type: Research paper